Female managers’ organizational leadership during telework: experiences of job demands, control and support - Nordhall, Ola; Kaur, Raman; Törnblom, Linnea; Knez, Igor (Frontiers in Psychology, 2024)
The frequent use of telework during the COVID -19 pandemic has created a more challenging work situation for managers who need to lead effectively in the virtual space, this especially concerns female managers. Therefor it is of importance to investigate female managers' experiences of job related demands, control and support within this work context. Accordingly, we investigated female managers' experiences of demands, control and support in their organizational leadership during telework. The present study used a deductive, theorydriven, qualitative approach with predetermined themes defined within the demand-controlsupport model. Data were collected by semi-structured interviews. The female managers had at least 50% of their working hours as telework. The results showed that the female managers experienced demands in terms of hard, fast or even excessive work in order to be available and solve complex problems, and control as varied work content, new learning, planning and decision freedom. Support was experienced in terms of attentive superior manager, good cooperation and helpfulness among colleagues. Theoretical and practical implications of the results are discussed in terms of telework situation for female managers.